THE EFFECT OF DIVIDEND PAYOUT RATIO, PROFITABILITY AND COMPANY SIZE ON DEBT POLICY IN NON-FINANCIAL STATE-OWNED ENTERPRISES IN INDONESIA PERIOD 2019-2023 - Fitriani; Darmawati Muchtar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to examine the effect of dividend payout ratio , profitability, and company size on debt policy in non-financial state-owned enterprises in Indonesia for the period 2019-2023. The data in this study were accessed through the official website www.idx.co.id. The sample used in this study was 19 companies. The data analysis method in this study used panel data regression analysis with the application tool eviews 12. The results of the study found that the dividend payout ratio influential significant negative impact on corporate debt policy in non-financial SOEs for the 2019-2023 period. Profitability has a significant negative effect on the company's debt policy in non-financial state-owned enterprises for the 2019-2023 period . Company size has a significant negative influence on the company's debt policy in non-financial BUMN for the 2019-2023 period